Dancing to the music of time: An experiential learning exercise in dementia care. (23rd August 2012) - Capstick, Andrea
This article presents findings from an experiential learning exercise in which 34 care practitioners enrolled on a part-time B.Sc. programme in Dementia Studies were asked to identify their own favourite music, and then to investigate the musical preferences of one of their clients with dementia. For both groups, practitioners and clients, three dominant themes influencing choice of music emerged: loving relationships; significant life events and places, and a sense of physical enjoyment. This exercise enabled the group of practitioners involved to identify commonalities between their own musical memories and those of their clients with dementia. They also uncovered considerable amount of new information about their client's life histories. On this basis they were able to make a number of new recommendations for improving care practice.